ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 14/PUU-XI/2013 TENTANG PENGUJIAN UNDANG-UNDANG NOMOR 42 TAHUN 2008 TENTANG PEMILIHAN UMUM PRESIDEN DAN WAKIL PRESIDEN TERHADAP UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Rudy Andika Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
In principle, in deciding the case of judicial review, the Constitutional Court can only act as a negative legislator, means that only the Constitutional Court can declare chapter, paragraph, section or all norms of law contrary to the Constitution of 1945, and is no longer have binding force. It is as defined in Article 56 and Article 54 of Law No. 8 of 2011 on the Constitutional Court. However, in the development, the Constitutional Court made several decisions that do not just cancel the norm, but also make the decision that is set (positive Legislature). In a normative juridical perspective, judicial activism actions that lead to positive position Legislature, is not in accordance with the article above and beyond the limits impressed. Yet, when examined, several decisions of the Constitutional Court which is positive and the Legislature would indicate evidence of progressive law enforcement.This type of research can be classified into types of normative legal research, namely the law library. In a study author conducted a study of the principles of law and legal systematics dotted benchmarks of areas specific legal system, by conducting the identification prior to the legal rules that have been formulated in the specific legislation, the data sources used, the data primary, secondary data, and the data tertiary.From the research, there are three main issues that can be inferred First, The Supreme Court judgment is a link between the system of elections and the presidential system of government, the original intent of the framer of the 1945 Constitution, as well as the effectiveness and efficiency of elections, as well as the right of citizens to vote intelligent. Second, the Constitutional Court Decision No. 14 / PUU-XI / 2013 in accordance with Law No. 8 of 2011 on the amendment of Act No. 24 of 2003 on the Constitutional Court and the Constitutional Court Procedural Law. Third, the legal implications of that happening is to change the electoral system itself and also resulted to the removal of the articles that were canceled and must be followed by the existence of a new law for the administration of elections itself, reduction in election funding and provide more space widely to the public to participate in the election itself and protect the rights of society. Suggestions writer, is expected to governments and the Commission to make regulations containing the results of the decision of the Constitutional Court Number 14 / PUU-XI / 2013..Keywords: Analysis - Decision of the Constitutional Court – Judicial Review - Constitution